(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Postpartum Depression (PPD) is considered to be a mental disorder. During pregnancy, women go through many changes in their lives, both emotional and physical, which are often not noticed by their support network and due to a lack of knowledge, making diagnosis very difficult. PPD affects around 15% to 20% of puerperal women who experience a number of alterations, such as a lack of family support, violence, mistimed pregnancies, low income, etc. Objective: To demonstrate the risk and protective factors in PPD through a literature review and to present issues pertinent to PPD through a literature review. Methodology: This research is a literature review. Results and conclusions: The results indicate that the protective factors include primary care, which helps prevent the disease, as well as a multidisciplinary team, family support, especially from the partner, and an understanding of what PPD is. The risk factors are many, ranging from anxiety, previous depression, low income and lack of support, among others. It can therefore be concluded that PPD is a serious but occasional mental disorder that affects women during the puerperium. However, it is a disease with a positive prognosis as long as treatment is carried out properly, with the support of a multidisciplinary team, social and family support.